Analytical and experimental determination of slug flow parameters, pressure drop and heat transfer coefficient in micro-channel condensation. (August 2017) - Liang, Gangtao; Mascarenhas, Nikhin; Mudawar, Issam
Highlights: Experiments are conducted involving condensation of FC-72 along micro-channels. Operating conditions are adjusted to yield slug flow along most of the channel length. New interfacial instability theory is developed to capture the transition from annular flow to slug flow. A theoretical slug flow model is constructed which shows very good heat transfer predictions. Abstract: This paper investigates slug flow associated with condensation along a module containing 10 of 29.9-cm long micro-channels having 1 × 1-mm 2 cross section. Using FC-72 as condensing fluid, which is cooled by water counterflow, experiments are performed to measure pressure drop as well as detailed temperature variations along the condensation module. Using high speed video, the flow is shown to consist of a series of unit cells, each comprised of a liquid slug and an elongated bubble. New interfacial instability theory is developed to describe the transition from annular flow to slug flow and obtain analytical expressions for bubble and slug lengths for the most upstream unit cell. Also presented is a new theoretical model for slug flow that is used to determine axial variations of bubble, slug and unit cell lengths. These lengths are used to evaluate axial variations of the local heat transfer coefficient, which are accurately predicted using the new model. Additionally, pressure drop data show good agreement with predictions of a recent universal correlation approach for condensation in small channels.